AN EXPERIMENTAL INVESTIGATION OF FLOW OVER PENTAGONAL CYLINDER - Ghosh, Kapil; Islam, Md. Quamrul; Ali, M (Journal of Mechanical Engineering, 2014)
In this research work, an experimental investigation of wind effect on pentagonal cylinders was carried out. The study was performed on the single cylinder in an open circuit wind tunnel at a Reynolds number of 4.22 x 104 based on the face width of the cylinder across the flow direction in a uniform flow velocity of 13.5 m/s. The test was carried out at various angles of attack from 0° to 63° at a step of 9°. The surface static pressures at the different locations of the cylinder were measured with the help of inclined multi-manometers. The wind velocity was kept constant at 13.5 m/s. The pressure coefficients were calculated from the measured values of the surface static pressure distribution on the cylinder. Later the drag and lift coefficients were obtained from the pressure coefficients by the numerical integration method. The results will enable the engineers and architects to design buildings more efficiently. Since the results will be expressed in the nondimensional form they may be applied for the prototype building. DOI: http://dx.doi.org/10.3329/jme.v44i1.19499